The multidimensional assessment of interoceptive awareness, version 2: Translation and psychometric properties of the Chinese version - Teng, Binyu; Wang, Dan; Su, Conghui; Zhou, Hui; Wang, Tengfei; Mehling, Wolf E.; Hu, Yuzheng (Frontiers in Psychiatry, 2022)
Background: The Multidimensional Assessment of Interoceptive Awareness (MAIA) is a self-report questionnaire developed by Dr. Mehling that has been widely used to assess multiple dimensions of interoceptive awareness. To further improve the MAIA, Mehling developed the Multidimensional Assessment of Interoceptive Awareness, Version 2 (MAIA-2). The goal of this study is to systematically translate the MAIA-2 into Chinese and to investigate the psychometric properties of the Chinese version (MAIA-2C). Methods: The translation and adaptation of the questionnaire was conducted according to Beaton’s method. A total number of 627 participants were enrolled and completed the survey. The entire sample was randomly divided into a training sample (n = 300, 47.8%) and a validation sample (n = 327, 52.2%) for a cross-validation. Exploratory factor analysis (EFA) was used to identify the factor structure of the MAIA-2C in the training sample while confirmatory factor analysis (CFA) was used to test the factor structure obtained by EFA. The reliability of the MAIA-2C was indicated by Cronbach’s alpha. The convergent and discriminant validity were assessed by Pearson intercorrelations between the MAIA-2C and the Five-Facet Mindfulness Questionnaire (FFMQ) and State-Trait Anxiety Inventory-Trait anxiety (STAI-T). Results: The EFA results showed an initial 10-factor model, but some items (1, 2, 3, 4, 15, 16) were deleted because they did not yield the original subscale construct. Eventually a 7-factor model represented the best model fit. The CFA results represented a good model (χ2/df = 2.170, RMSEA = 0.060, SRMR = 0.0810, CFI = 0.890). The Cronbach’s alpha was 0.822 for the total scale and ranged from 0.656 to 0.838 for the subscales. The results of convergent and discriminant validity showed that most MAIA-2C subscales were correlated with the total and subscales of FFMQ (r = -0.342 ~ 0.535, p < 0.05), and all of the subscales of the MAIA-2C showed negative correlations with the STAI-T total score (r = -0.352 ~ -0.080, p < 0.05). Conclusion: The MAIA-2C is a valid and reliable instrument for evaluating multiple dimensions of interoceptive awareness in a Chinese population.